Adaptation of Kangaroo Mother Care for community-based application - Quasem, Md. Iftekhar; Sloan, Nancy L.; Chowdhury, Anita; Ahmed, Salahuddin; Winikoff, Beverly; Chowdhury, A. M. R. (BRAC Research and Evaluation Division (RED), 2019)
Objective: Working with a multi-disciplinary team of Ecuadorians, Bangladeshis and Americans, we developed a simple protocol for community-based implementation of kangaroo mother care (CKMC) that does not require birth weight or clinical judgment to identify which newborns should receive CKMC. CKMC could stabilize newborns and possibly reduce neonatal mortality where there is little medical care for newborns and low birth weight (LBW) is common. Study Design: During their CKMC training, community-based workers identified 35 expectant or recently delivered women in the pilot study area and taught them about CKMC. Women were interviewed at one month postpartum to evaluate their experience with CKMC. Results: 77% of mothers initiated skin-to-skin care and 85% with LBW babies did so (37% were LBW). CKMC mothers delayed newborn bathing. Few slept upright with their newborns. Conclusions: CKMC was quickly and popularly adopted. A randomized controlled cluster trial is planned to determine whether CKMC reduces neonatal mortality.